“The power of producing wealth, infinitely more important than wealth itself” – the truth transforming the current international order - Paul Dobrescu; Mălina Ciocea (Romanian Journal of European Affairs)
This paper discusses the causes of the imbalance that characterises the postcrisis world by looking at manufacturing capacities, public debt and trade deficit. It analyses the spectacular transformations taking place nowadays in liberal international order: rapid changes in the structure of global power and in the hierarchy of various countries and regions in international economy and trade. The article shows that while historically the hegemonic power defended the order it had instituted, in today’s world the US encourages bilateralism, and not multilateralism (one of the fundamental traits of globalization). Pro-globalization voices now belong to other contenders in the global economic race (like China).